2017
DOI: 10.2139/ssrn.2994757
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur Abatement Globally in Maritime Shipping

Abstract: In 2016, the International Maritime Organization (IMO) decided on global regulations to reduce sulphur emissions to air from maritime shipping starting 2020. The regulation implies that ships can continue to use residual fuels with a high sulphur content, such as heavy fuel oil (HFO), if they employ scrubbers to desulphurise the exhaust gases. Alternatively, they can use fuels with less than 0.5% sulphur, such as desulphurised HFO, distillates (diesel) or liquefied natural gas (LNG). The options of lighter fue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…In the case of Finland, one of such routes has been very short -sea connection from Helsinki to Tallinn, and from there on with truck to Poland, Germany or somewhere else in Central and Eastern Europe. This shift has been caused by increased sea transportation costs due to sulphur regulation and higher priced maritime diesel oils (or using scrubbers, million euro investment on single ship; Lindstad et al, 2017). Third reason is the competition of major sea container hub, and therefore Finnish export containers do not end up to German sea ports, but e.g.…”
Section: Unitized Maritime Flows Between Finland and Germanymentioning
confidence: 99%
“…In the case of Finland, one of such routes has been very short -sea connection from Helsinki to Tallinn, and from there on with truck to Poland, Germany or somewhere else in Central and Eastern Europe. This shift has been caused by increased sea transportation costs due to sulphur regulation and higher priced maritime diesel oils (or using scrubbers, million euro investment on single ship; Lindstad et al, 2017). Third reason is the competition of major sea container hub, and therefore Finnish export containers do not end up to German sea ports, but e.g.…”
Section: Unitized Maritime Flows Between Finland and Germanymentioning
confidence: 99%
“…Equation (8), by estimating the BSFC relative change according to Equation (5). Since the fuel injection 9 timing also influences the scavenging receiver pressure (variation up to 6% as can be inferred from Fig.…”
Section: Incorporation Of the Derived Corrective Equations In The Mvementioning
confidence: 99%
“…Table 3 Percentage errors of the predicted parameters against experimental data from shop trials. Table 4 Coefficients values for Equations (3), (4) and (5). Table 5 Constants of Equation (10).…”
Section: Settings 11mentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, Zis, et al [7] found that the scrubber installation reduces the ship operating cost; however, the lower bunker prices delay the payback period of a scrubber investment. In addition, the findings of Jiang, et al [8] and Lindstad, et al [9] indicate that a scrubber is a better compliance option when the price spread between heavy fuel oil (HFO) and MGO is high (more than 231 Euros per ton), when the remaining lifespan of a vessel is more than 4 years, and when the vessel operates on a long-distance route with high fuel consumption.…”
Section: Introductionmentioning
confidence: 99%